PENINGKATAN KEPUASAN PELANGGAN ULP BOJONEGORO KOTA TERHADAP PELAYANAN TAMBAH DAYA DAN MIGRASI MELALUI PLN MOBILE - Sa’adah, Badi Atus; Samsudin, Acep (Jurnal Bisnis Indonesia, 2024)
Customer decisions are one of the main priorities of a company, because a company can be said tohave succeeded in developing if it has been able to provide service satisfaction to its customers. Tocontinue to increase customer service satisfaction, PT PLN (Persero) presents an application that willhelp in its service, namely PLN Mobile. This PLN Mobile application is an official applicationlaunched and provided by PLN (State Electricity Company) to provide services to customers inaccessing information regarding Electricity Bills, Electricity Usage, Complaints, Self-Record MeterNumbers (SWACAM), Electricity Usage Monitor, Power Addition Services , and Switching from Pacsaelectricity to Prepaid (Migration) and vice versa from Prepaid and Postpaid. With the launch of PLNMobile, it is hoped that it will be more helpful and increase customer service satisfaction.Keywords: Increased Customer Satisfaction; PLN Mobile; Customer service